Model Penalaran Matematika Formal Siswa Dalam Memecahkan Masalah Fisika - Nurrahmah Nurrahmah; , Darsikin , Darsikin; Amiruddin Kade (Mitra Sains, 2019)
This research is qualitative used descriptive method for analyzing the use of formal mathematics reasoning in solving physics problems. Subjects of the research were nine students of SMA Al-Azhar Palu which consisted of three categories in ability, i.e: high, moderate and low category. Research instruments consisted of respondent test selection and interview protocol. Data collection was carried out through recording (by handycame) on thinking-aloud and interview activities. based on data analysis, it could be stated that obtained formal mathematics reasoning includes completeness and repetition in reasoning. It is needed development of learning that considers the important of the use formal mathematics reasoning as framework for evaluating a progress of student’s problem solving.